2014
DOI: 10.1093/nar/gku993
|View full text |Cite
|
Sign up to set email alerts
|

The intrinsically disordered amino-terminal region of human RecQL4: multiple DNA-binding domains confer annealing, strand exchange and G4 DNA binding

Abstract: Human RecQL4 belongs to the ubiquitous RecQ helicase family. Its N-terminal region represents the only homologue of the essential DNA replication initiation factor Sld2 of Saccharomyces cerevisiae, and also participates in the vertebrate initiation of DNA replication. Here, we utilized a random screen to identify N-terminal fragments of human RecQL4 that could be stably expressed in and purified from Escherichia coli. Biophysical characterization of these fragments revealed that the Sld2 homologous RecQL4 N-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 75 publications
4
65
0
1
Order By: Relevance
“…However, Hrq1 unwinding of forks with poly(dT)-tails of 25-, 50-, and 75-nt in length was indistinguishable, indicating that long (!70 nt) 3'-tails are not required for robust helicase activity. Finally, we demonstrated that the strong DNA strand annealing and exchange activities previously reported for RecQ4 [5] are absent in Hrq1.…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…However, Hrq1 unwinding of forks with poly(dT)-tails of 25-, 50-, and 75-nt in length was indistinguishable, indicating that long (!70 nt) 3'-tails are not required for robust helicase activity. Finally, we demonstrated that the strong DNA strand annealing and exchange activities previously reported for RecQ4 [5] are absent in Hrq1.…”
Section: Introductionsupporting
confidence: 61%
“…Strand annealing activity is attributed to the Sld2-like N-terminal domain of RecQ4 [5,17], which is further supported by the demonstrated DNA annealing activity of S. cerevisiae Sld2 [4]. We previously found no hint of DNA strand annealing by Hrq1 [8], presumably because it does not contain a Sld2-like domain.…”
Section: Hrq1 Does Not Possess Ssdna Annealing Activitysupporting
confidence: 52%
See 3 more Smart Citations